Pathophysiology of heart failure and its relationship with interleukin - 1β sST2 receptors - Menegassi, Felipe Gustavo Morais (Seven Editora, 2024)
Objective: to establish, through a narrative-critical review, the pathophysiology, prevalence, diagnosis and therapeutic management of heart failure (HF). It also demonstrated the association of HF with cardiovascular biomarkers, such as interleukin 1β and its receptors. Methods: literature review based on scientific articles from the PubMed, LILACS and SciELO databases. Descriptors based on studies published in the years 2014 to 2023 and adherence to the theme "heart failure" were used. Studies without complete publications and without free availability on the data platform were excluded. Results: 204, 22 and 6 articles were obtained from the PubMed, LILACS and SciELO databases, respectively. Of these, 18, 2 and 2 articles from PubMed, LILACS and SciELO, respectively, stood out after evaluation and use of exclusion criteria. Finally, 17 articles and a textbook make up this study. Conclusion: HF is a syndromic pathology caused by a series of different etiological diagnoses. Patients with HF have several compensatory mechanisms, in addition to occasional cardiac remodeling and repair guided by inflammatory mediators. In this disease, biomarkers are very useful, being widely studied in recent years. An important highlight is the 1β interleukins, which are useful in the diagnosis and therapeutic management of HF. DOI:https://doi.org/10.56238/sevened2024.018-045